(untitled) (Journal of Nepal Geological Society, 2025)
Anisotropy of magnetic susceptibility (AMS) was determined in the impure marly carbonates from 26 sites within the Tethys Himalaya (Tambakurkur (TKF) and Mukut Limestone (MLF) Formations; Triassic age) in upper Dolpo, WesternNepal. Excluding one anomalous site, the average magnetic susceptibility for 25 sites has a range of (76.6±23.7 to 240.3±11.1) ×10-6 SI. Average Jelinek’s degree of anisotropy was weak (1.013-1.049), while the AMS ellipsoid shaperanged from moderately prolate to weakly oblate. Ferro(i)magnetic minerals (magnetite with its maghemitized derivatives and pyrrhotite) contributed to remanence. These together with diamagnetic (e.g., calcite) and paramagnetic (e.g., phyllosilicates) minerals contributed to the AMS. Distribution of Principal AMS axes reveals three distinctmagnetic fabric patterns (MFPs): (i) A tectonic fabric (MFP1) represented by NE-SW directed magnetic lineations (kmaxaxes) with shallow plunges dominantly to SW (before) or NE (after) bedding tilt-correction) and preferably NW or SE directed shallow plunging kmin axes implying a sub-vertical NE-SW magnetic foliation; (ii) A second pattern (MFP2),also of tectonic origin, in which the kmax axes exhibit shallow plunge mainly towards N or S and the kmin form girdles along an E-W plane (in situ) but align mainly towards E or W after bedding-tilt correction; (iii) a third pattern (MFP3),with the kmax axes orthogonal to bedding (S0) that is subparallel to the girdle defined by the other two axes (kint andkmin) representing an inverse structural magnetic fabric. MFP1 was clearly acquired before folding, while MFP2 developed during a longer period of active/progressive folding. MFP1 with the mean trend of kmax at N46°E (after fold plunge and bedding correction) is interpreted as the reflection of mineral stretching lineation (known from rocks of relatively high grade metamorphics in adjoining areas) formed simultaneously and/or prior to the earliest Eo-Himalayan (D1 and/or D2) deformation events. MFP2, with the mean corrected trend of kmax axes at N4°W, is inferred to post-datethe MFP1 and correspond to Neo-Himalayan deformation events which promoted thermo-chemical transformations leading to the production of pyrrhotite. Thus, while MFP1&2 are directly related to the tectonic history of the Higher Himalaya, MFP3 is an inverse structural magnetic fabric, likely controlled by uni-axial/elongated single-domain magnetite grains.